The Role of Islam in the Yoruba-Hausa Harmonious Relations in Southwestern Nigeria (IIUC Studies, 2016)
In Nigeria, academic discourse on inter-group relations over the years has been narrowed down to only two interrelated terms: conflict and violence. This is due to the rising cases of inter-ethnic and inter-religious conflicts witnessed in the multi-cultural and multi-religious Nigeria. This paper intends to argue that the escalating ethnic and religious consciousness is greatly the handiwork of elites and politicians who employ both ethnicity and religion as effective tools for mass mobilization and manipulation of citizens psyche in their attempt to dominate the state power apparatus and resources. It also affirms the view that, as far as the Yoruba and Hausa communities of Agege are concerned, a high level of cordial inter-group relations had been achieved, owing to inter-communal mechanisms developed amongst the Yoruba and Hausa communities over the years of interaction. One of the effective vehicles through which the cordial inter-communal relations are achieved is Islam.IIUC Studies Vol.12 December 2015: 111-126